Dealing with religious difference in kindergarten - Helena Stockinger (Religious Diversity and Education in Europe, 2018)
In kindergartens children of different religions and with different religious attitudes meet, play and learn together. How do kindergartens deal with religious differences and how do children address this topic? The ethnographic study reported in this book explores this question in two kindergartens, one run by a Catholic, the other by an Islamic organization. The results illustrate how important it is to handle religious difference attentively. In order to reduce structural discrimination, the author considers how a culture of recognition can be developed, with religious difference being given the attention it requires. This book provides a valuable contribution to a difference-sensitive interaction in educational institutions.